Design and analysis of high efficiency line drivers for xDSL - Piessens, Tim (Kluwer international series in engineering and computer science ;, 2004)
Design and Analysis of High Efficiency Line Drivers for xDSL covers the most important building block of an xDSL (ADSL, VDSL ...) system: the line driver. Traditional Class AB line drivers consume more than 70% of the total power budget of state-of-the-art ADSL modems. This book describes the main difficulties in designing line drivers for xDSL. The most important specifications are elaborated staring from the main properties of the channel and the signal properties. The traditional (class AB), state-of-the-art (class G) and future technologies (class K) are discussed. The main part of Design and Analysis of High Efficiency Line Drivers for xDSL describes the design of a novel architecture: the Self-Oscillating Power Amplifier or SOPA.